Adolescent Fertility and Child Health: The Interaction of Maternal Age, Parity and Birth Intervals in Determining Child Health Outcomes - Finlay, Jocelyn E.; Norton, Melanie K.; Guevara, Iván Mejía- (International Journal of Child Health and Nutrition, 2017)
Introduction: Contributing to the Sustainable Development Goals, Global Goals, Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-2030, we clarify the interaction between maternal age, parity and birth intervals to examine the effects on child health. Methods: We use Demographic and Health Survey data from 33 sub-Saharan African countries, and apply multivariate Poisson and logistic models to first examine the effect of maternal age (15-17, 18-19, 20-24, 25-29, 30-39) on infant mortality and stunting, then modify this relationship by parity and account for the confounding effects of short birth intervals. Results: We find that poor infant mortality outcomes of children born to teen mothers are driven by higher parity children, not first-born children. While first-born children of teen mothers are at a high risk of stunting, they are likely to survive. Short birth intervals have a negative effect on infant survival and stunting outcomes. But controlling for short birth intervals does not completely offset the effect of young age at birth on child survival outcomes. Discussion: High parity children of young mothers are at a high risk of infant mortality, driven in part – but not completely – by short birth intervals. Policies aimed at delaying first birth are warranted, but should not overshadow the need to support adolescent mothers at risk of multiple births that are tightly spaced.